Розширювальне тлумачення норм національного і міжнародного права - Волошенюк, О. В.; Volosheniuk, O. V.; Волошенюк Олександр Володимирович (Форум права. - 2024. - № 1(78). - С. 77-87, 2024)
Надано поглиблену характеристику розширювального тлумачення норм права з урахуванням сучасних тенденцій розвитку національної та міжнародної юридичної теорії і практики. Встановлено, що використання розширювального тлумачення спричинене чотирма групами чинників: значна кількість фактичних обставин, з якими правове регулювання має справу; динамізм суспільних відносин, які регулюються правом; наявність різних правових культур і методологічних підходів до інтерпретації правових приписів; динамізм права, що проявляться у поступовій зміні правових цінностей і пріоритетів. Це дозволило виокремити такі його види, як змістовно-фактичне, темпоральнофактичне, змістовно-правове і темпорально-правове. Аналіз інтерпретаційної практики свідчить про те, що вказані різновиди розширювального тлумачення використовуються суб’єктами тлумачення норм як національного, так і міжнародного права. Діяльність національних конституційних судів, Міжнародного суду ООН, Європейського суду з прав людини в сучасних умовах зорієнтована на адаптацію нормативних текстів до реалій сьогодення, внаслідок чого еволюційне, динамічне тлумачення закону чи міжнародного договору стає все більш затребуваним.

Law is aimed at harmonizing a wide range of dynamic and unpredictable social relations, which prompts law-making subjects to use different degrees of specification of legal norms. In the process of implementation of the current regulatory and legal array, there is an objective need to establish the valid content of each legal norm, that is, its interpretation. Despite a significant number of scientific works on the researched topic, there are still many questions that have not found adequate coverage in the scientific literature. This, in particular, concerns the general theoretical characteristics of certain types of interpretation of legal norms by scope, which is presented schematically and not fully enough in the available sources. Therefore, the purpose of the article is an in-depth characterization of the expanding interpretation of legal norms, taking into account the current trends in the development of national and international legal theory and practice. Methods. With the help of system-factor analysis, a study of the influence of various factors on the process of interpretation of legal texts was carried out. The comparative legal method made it possible to compare the understanding of some legal categories in Germany and Ukraine. The historical method made it possible to highlight the development of evolutionary interpretation in the practice of the UN International Court of Justice and the European Court of Human Rights. Results. It has been established that four groups of factors cause the use of extended interpretation: a significant number of factual circumstances with which legal regulation deals; the dynamism of social relations regulated by law; the presence of different legal cultures and methodological approaches to the interpretation of legal prescriptions; the dynamism of law, which manifests in the gradual change of legal values and priorities. This made it possible to distinguish its types, such as content-factual, temporal-factual, content-legal, and temporal-legal. Conclusions. The analysis of interpretive practice shows that subjects of interpretation of national and international law norms use the specified varieties of extended interpretation. The activities of national constitutional courts, the International Court of the United Nations, and the European Court of Human Rights in modern conditions are oriented towards the adaptation of normative texts to the realities of today, because of which the evolutionary, dynamic interpretation of a law or an international treaty is becoming more and more in demand.

Дана углубленная характеристика расширительного толкования норм права с учетом современных тенденций развития национальной и международной юридической теории и практики. Установлено, что использование расширительного толкования обусловлено четырьмя группами факторов: значительное количество фактических обстоятельств, с которыми правовое регулирование имеет дело; динамизм общественных отношений, регулируемых правом; наличие разных правовых культур и методологических подходов к интерпретации правовых предписаний; динамизм права, проявляющийся в изменении правовых ценностей и приоритетов. Это позволило выделить такие его виды, как содержательно-фактическое, темпорально-фактическое, содержательно-правовое и темпорально-правовое.
Extended interpretation of national and international law norms
Keywords: тлумачення норм права; розширювальне тлумачення; еволюційне тлумачення; динамічне тлумачення; Міжнародний суд ООН; Європейський суд з прав людини; interpretation of legal norms; extended interpretation; evolutionary interpretation; dynamic interpretation; UN International Court of Justice; European Court of Human Rights; толкование норм права; расширительное толкование; эволюционное толкование; динамическое толкование; Международный суд ООН; Европейский суд по правам человека